ShapeTouch: Leveraging Contact Shape on Interactive Surfaces - Wilson, Andy; Hinckley, Ken; Cao, Xiang; Balakrishnan, Ravin; Hudson, Scott E. (Horizontal Interactive Human Computer Systems, 2008. TABLETOP 2008. 3rd IEEE International Workshop on, 2008)
Many interactive surfaces have the ability to detect the shape of hands or objects placed on them. However, shape information is typically either condensed to individual contact points or categorized as discrete gestures. This does not leverage the full expressiveness of touch input, thus limits the actions users can perform in interactive applications. We present ShapeTouch, an exploration of interactions that directly utilize the contact shape on interactive surfaces to manipulations of objects and interactors. ShapeTouch infers virtual contact forces from contact regions and motion to enable interaction with virtual experiences of interacting with real physical objects.